Development and Application of EST-SSR Markers in Cephalotaxus oliveri From Transcriptome Sequences - Liu, Hanjing; Zhang, Yuli; Wang, Zhen; Su, Yingjuan; Wang, Ting (Frontiers in Genetics, 2021)
Cephalotaxus oliveri is an endemic conifer of China, which has medicinal and ornamental values. However, limited molecular markers and genetic information are insufficient for further genetic studies of this species. In this study, we characterized and developed the EST-SSRs from transcriptome sequences for the first time. The results showed that a total of 5089 SSRs were identified from 36446 unigenes with a density of one SSR per 11.1 kb. The most common type was trinucleotide repeats excluding mononucleotide repeats, followed by dinucleotide repeats. AAG/CTT and AT/AT exhibited the highest frequency in the trinucleotide and dinucleotide repeats, respectively. Of the identified SSRs, 671, 1125 and 1958 SSRs were located in CDS, 3’UTR and 5’UTR, respectively. Functional annotation showed that the SSR-containing unigenes were involved in growth and development with various biological functions. Among successfully designed primer pairs, 238 primer pairs were randomly selected for amplification and validation of EST-SSR markers, and 47 primer pairs were identified as polymorphic. Finally, 28 high polymorphic primers were used for genetic analysis and revealed a moderate level of genetic diversity. Seven natural C. oliveri populations were divided into two genetic groups. Furthermore, the 28 EST-SSRs had 96.43%, 71.43% and 78.57% of transferability rate in Cephalotaxus fortune, Ametotaxus argotaenia and Pseudotaxus chienii, respectively. These markers developed in this study lay the foundation for further genetic and adaptive evolution studies in C. oliveri and related species.